2019
DOI: 10.1002/mrm.28132
|View full text |Cite
|
Sign up to set email alerts
|

Motion and eddy current–induced signal dephasing in in vivo cardiac DTI

Abstract: Purpose To address motion in cardiac DWI, stimulated‐echo acquisition mode (STEAM) and second‐order motion‐compensated spin‐echo (SE) sequences have been proposed. Despite applying motion‐compensation strategies, residual motion can cause misleading signal attenuation. The purpose of this study is to estimate the motion‐induced error in both sequences by analysis of image phase. Methods Diffusion‐weighted motion‐compensated SE sequences and STEAM imaging was applied in vivo with diffusion encoding along 3 orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…As we have demonstrated, the use of an isolated perfused heart allows straightforward colocalisation of the imaging data and blocks of tissue used for histology. Future studies may include investigation of the effectiveness of motion compensation provided by the STEAM sequence by comparing the phase images between equivalent beating and arrested heart data, in a manner similar to Stoeck et al 47 Beyond the investigation of CMR methods, we believe this CMR-compatible isolated perfused beating large animal heart model has potential use in assessing myocardial tissue engineering methods, cardiac regeneration therapy and in joint imaging-electrophysiology studies. 48 There are a number of limitations to this study, in addition to the myocardial oedema and apparent failure to achieve microstructural relaxation, as discussed above.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As we have demonstrated, the use of an isolated perfused heart allows straightforward colocalisation of the imaging data and blocks of tissue used for histology. Future studies may include investigation of the effectiveness of motion compensation provided by the STEAM sequence by comparing the phase images between equivalent beating and arrested heart data, in a manner similar to Stoeck et al 47 Beyond the investigation of CMR methods, we believe this CMR-compatible isolated perfused beating large animal heart model has potential use in assessing myocardial tissue engineering methods, cardiac regeneration therapy and in joint imaging-electrophysiology studies. 48 There are a number of limitations to this study, in addition to the myocardial oedema and apparent failure to achieve microstructural relaxation, as discussed above.…”
Section: Discussionmentioning
confidence: 96%
“…As we have demonstrated, the use of an isolated perfused heart allows straightforward colocalisation of the imaging data and blocks of tissue used for histology. Future studies may include investigation of the effectiveness of motion compensation provided by the STEAM sequence by comparing the phase images between equivalent beating and arrested heart data, in a manner similar to Stoeck et al 47 …”
Section: Discussionmentioning
confidence: 99%
“…Because DW‐STEAM sequences do not require strong gradient systems, diffusion gradient‐induced eddy currents were assumed to be negligible. 54 Their approach of measuring field maps using a low‐resolution spiral for each acquisition could capture both static and variations in a convenient manner. The lower resolution of the field map, however, would not allow to correct for issues at tissue interfaces.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Furthermore, DTI relies on low SNR DW images, leading to errors in measured parameters, 24 , 25 and sensitivity to image resolution and SNR. 26 The low SNR necessitates larger voxel sizes that enhance partial volume and residual motion artefacts, 27 while the rapid switching of diffusion gradient waveforms may enhance eddy current effects. 27 Additionally, early STEAM studies erroneously ascribed b‐values of 0 s/mm 2 to the non‐DW data during the reconstruction, leading to bias in MD, even within one sequence type.…”
Section: Introductionmentioning
confidence: 99%
“… 26 The low SNR necessitates larger voxel sizes that enhance partial volume and residual motion artefacts, 27 while the rapid switching of diffusion gradient waveforms may enhance eddy current effects. 27 Additionally, early STEAM studies erroneously ascribed b‐values of 0 s/mm 2 to the non‐DW data during the reconstruction, leading to bias in MD, even within one sequence type. 28 , 29 Consequently, studies in the myocardium of healthy volunteers have reported a wide range of MD (0.87 x 10 −3 to 1.72 x 10 −3 mm 2 /s) and FA (0.29 to 0.61).…”
Section: Introductionmentioning
confidence: 99%